CD44v6 coordinates tumor matrix-triggered motility and apoptosis resistance - Jung, Thorsten; Gross, Wolfgang; Zöller, Margot (The journal of biological chemistry, 2011)
Tumor progression requires a crosstalk with the tumor surrounding, where the tumor matrix plays an essential role. We recently reported that only the matrix delivered by a CD44v6-competent (ASMLwt), but not that of a CD44v6-deficient (ASML-CD44vkd) rat pancreatic adenocarcinoma line supports metastasis formation. We here describe that this matrix provides an important feedback toward the tumor cell and that CD44v6 accounts for orchestrating signals received from the matrix. ASMLwt cells contain more hyaluronan synthase-3 and secrete higher amounts of >50 kDa HA than ASML-CD44vkd cells, which secrete more hyaluronidase. Only the ASMLwt-matrix supports migration and apoptosis resistance, which both can be initiated via CD44v6, c-Met, and α6β4 ligand binding and proceed via FAK, PI3K/Akt, and MAPK activation, respectively. However, c-Met- and α6β4-initiated signaling are strongly augmented by the association with CD44v6 as only very weak effects are observed in CD44v6-deficient cells. The same CD44v6-dependent convergence of motility- and apoptosis resistance-related signals also accounts for human tumor lines. Thus, CD44v6 promotes motility and apoptosis resistance via its involvement in assembling a matrix that, in turn, triggers activation of signaling cascades, which proceeds, independent of the initiating receptor-ligand interaction, in a concerted action via CD44v6.
Gesehen am 05.07.2022